Identitas Keturunan Perempuan Dalam Kejadian 3:15 Dalam Studi Soteriologi - Pangeran Manurung (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
One of the problems arising from the polemic of the events of the fall of man in the Garden of Eden recorded by the author of the Book of Genesis is the bias of the policy of salvation taught by the writers of the New Testament. Salvation in the New Testament is considered not to have originated in the Old Testament mind. Apart from the element of salvation in the Old Testament which is only supposed to contain